2012
DOI: 10.2989/1814232x.2012.675126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemicals from longline baits on the biting behaviour of loggerhead sea turtles

Abstract: The biting behaviour of the loggerhead sea turtle Caretta caretta, a high bycatch species by longline fishing gear, was studied on 30 wild specimens held temporarily at rescue centres. To account for repeated measures, the data were analysed using mixed-effects models. Chemicals from squid baits elicited significantly more biting behaviour than those from mackerel baits. Smaller turtles were more likely to bite than larger turtles. The findings add increasing evidence in support of the idea that the use of fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…There have been conflicting findings on the effect of using fish vs. squid species for bait on catch rates of individual teleost and elasmobranch species, but relatively consistent findings that using small fish species for bait reduces sea turtle catch rates relative to using squid for bait (Broadhurst and Hazin, ; Watson et al ., ; Mejuto et al ., ; Yokota et al ., ; Coelho et al ., ; Foster et al ., ; Piovano et al ., ; Santos et al ., ; Amorim et al ., ; Clarke et al ., ). A few studies have observed that using fish instead of squid for bait significantly increased the proportion of some species of caught sharks that were deeply hooked, with the opposite effect for swordfish (Broadhurst and Hazin, ; Watson et al ., ; Epperly et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting findings on the effect of using fish vs. squid species for bait on catch rates of individual teleost and elasmobranch species, but relatively consistent findings that using small fish species for bait reduces sea turtle catch rates relative to using squid for bait (Broadhurst and Hazin, ; Watson et al ., ; Mejuto et al ., ; Yokota et al ., ; Coelho et al ., ; Foster et al ., ; Piovano et al ., ; Santos et al ., ; Amorim et al ., ; Clarke et al ., ). A few studies have observed that using fish instead of squid for bait significantly increased the proportion of some species of caught sharks that were deeply hooked, with the opposite effect for swordfish (Broadhurst and Hazin, ; Watson et al ., ; Epperly et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These are possible factors explaining differences in catch rates between pelagic species and between sizes of individual pelagic species on fish versus squid for bait (Lokkeborg and Bjordal 1992;Broadhurst and Hazin 2001;Ward and Myers 2007;Yokota et al 2009). Hardshelled turtles may prefer squid to finfish due to natural chemical attractants present in squid (Piovano et al 2004(Piovano et al , 2012.…”
Section: Bait Typementioning
confidence: 99%
“…In particular, since physical forcings are among the main drivers of zooplankton dispersal [91], geophonic components like wind intensity might indirectly inform sea turtles about the presence of macro-and mega-zooplankton brought to the coast by higher wind intensity. The use of sensory stimuli by hard-shell sea turtles to orient towards their food choice has been proven chemically [92][93][94] and visually [95][96][97], and might extend to the use of acoustic stimuli. Comparison between geophonies, the abundance of planktonic food, and sea turtle spatial behavior recorded via satellite tracking would help clarify the effect of wind intensity on sea turtle behavior.…”
Section: Discussionmentioning
confidence: 99%